Stimulating Children’s Physical Play through Augmented Reality Game - Mohamad Daud, Nor Farah Naquiah; Abdullah, Muhammad Haziq Lim (Journal of Advanced Computing Technology and Application (JACTA), 2020)
Physical play includes activities that use physical movement to allow children to perform any task and helps children to develop gross and fine motor skills, learn new things, and socialize. The Child Development Institute stated that physical plays help children to develop connections between the nerve cells and the brain as 75 percent of brain development occurs after birth. Nowadays, children prefer indoor activities compared to outdoor activities, and this might harm their physical play as they become more passive and introverted. Hence, this project aims to design and develop a mobile game using augmented reality technology to foster children’s attention and interest to stimulate their physical play. This paper specifically explores how a mobile game with augmented reality technology can stimulate children’s physical play. This project has identified three findings corresponding to the themes related to the AR mobile game in supporting children’s physical play. The findings are i) AR games can stimulate physical interaction among children; ii) AR games can increase cognitive and memory skills development among children and iii) AR games can help children to have better interaction with real-world context. Thus, mobile games with augmented reality technology can support simulating children’s physical play.